Arsenic Oxidation and Its Subsequent Removal from Water: An Overview - Sanchez-Poblete, J; Alsamman-, M (Elsevier B.V., 2023)
Public water pollutants such as arsenic are dangerous to human health with severe or long-term effects, e.g., they can cause cancer, poison the nervous system, or result in diabetes and many diseases. The World Health Organization (WHO) has determined that the highest permissible concentration for arsenic is 10 µg/L. Arsenic in water mainly exists with two oxidation states: As(III) and As(V), with As(V) being an oxyanion in a wide range of pH values. However, As(III) is a neutral species that is mobile and difficult to remove by traditional adsorbents and technologies. Thus, the oxidation of As(III) to As(V) is considered an important pretreatment to improve the arsenic removal. In this review, we focus on different materials and techniques that promote the efficient oxidation of As(III) to As(V). The most used anodes are those that electrocatalytically oxidize arsenic, which are mainly platinum, zinc, aluminium, magnesium, carbon, and artificial graphite. In the literature, through the anodes, oxidation and conversion of As(III) to As(V) occur, and the best anodes contain platinum or titanium because of their oxidation capacity of 99% and the ability to be used for long periods. In terms of efficiency, gold and diamonds can be added to platinum and other materials to improve the oxidation process. The oxidation process via anodes is not sufficient to remove arsenic, and arsenic cannot be precipitated through oxidation and forms soluble suspensions within the solutions. Instead, oxidation is considered to facilitate for the removal process and applied before other operations. As(V) is removed using adsorption, biological techniques, membranes, coagulation, electrocoagulation (EC), etc. However, the adsorption materials and biological techniques are not good for large quantities, and studies have proven that the methods of membranes and coagulation are less effective and slow in adsorbing arsenic than EC but successfully remove arsenic after the oxidation process. EC is the most common method for removing arsenic; it has a maximal efficiency of 96% at doses up to one litre and different concentrations. In the case of hybrid methods such as electro-oxidation with polymer enhanced ultrafiltration (PEUF), the use of cationic water soluble polymers showed a percentage of up to 100% of arsenic removal after a good performance in the previous electrocatalytic oxidation of As(III) to As(V). © 2022 Elsevier B.V.